2010
DOI: 10.1007/s10565-010-9154-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p44/42 MAPK plays a role in the TBT-induced loss of human natural killer (NK) cell function

Abstract: Natural Killer (NK) cells destroy (lyse) tumor cells, virally infected cells and antibody-coated cells. Previous studies indicated that exposure to the environmental contaminant tributyltin (TBT) decreases the lytic function of NK cells and activates mitogen activated protein kinases (MAPK), including p44/42 (Aluoch and Whalen, 2005). If activation of p44/42 is required for TBT-induced decreases of lytic function, then activation of p44/42 to similar extents by pharmacological agents such as Phorbol 12-myrista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…Stimulation of p44/42 (to an extent similar to what was seen with TBT) (Aluoch and Whalen 2005; Aluoch et al , 2006) was able to decrease NK lytic function in a manner similar to that seen with TBT (Dudimah et al , 2010). …”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Stimulation of p44/42 (to an extent similar to what was seen with TBT) (Aluoch and Whalen 2005; Aluoch et al , 2006) was able to decrease NK lytic function in a manner similar to that seen with TBT (Dudimah et al , 2010). …”
Section: Introductionmentioning
confidence: 75%
“…Exposure of NK cells to this concentration of PMA resulted in a significant loss of the cell-surface proteins CD11a, CD16, CD18, and CD56 (P<0.05) compared to the control. 2.5 nM PMA has previously been shown to activate p44/42 in NK cells by approximately 10 fold (Dudimah et al , 2010). The treatment resulted in expression of CD11a at a level of 30% of that seen in control cells (a 70% loss of CD11a), CD16 expression was 17% of control (83% decrease), CD18 was expressed at 37% of control levels (63% decrease), and CD56 expression was 50% of control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased expression of cell surface proteins involved in the cytotoxic process was also seen following activation of p44/42 by PMA (Dudimah et al, 2010b). Both TBBPA and HBCD were able to activate p44/42 and we have shown previously that activation of p44/42 decreases NK lytic function (Dudimah et al, 2010a). Thus, activation of this pathway appears to part of the mechanism by which these flame retardants diminish NK function.…”
Section: Discussionmentioning
confidence: 67%
“…Those studies showed that inhibition of the p44/42 pathway by the MEK inhibitor PD98059 blocked NK cell mediated destruction of tumor cells as well as target stimulation of interferon gamma (IFNγ) synthesis. Additionally, we have previously shown that activation of p44/42 in NK cells by phorbol 12 myristate 13 acetate (PMA) prior to their contact with target cells rendered the NK cell unable to lyse the target cells (Dudimah et al, 2010a). This loss of function was seen within an hour of p44/42 activation (Dudimah, et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%